AI as a patient educator: Evaluating ChatGPT’s role in disseminating information on herpes zoster ophthalmicus - Yigen İritaş, Seçil and İritaş, İlter (The European Research Journal, 2025)
Objectives: The aim of this study is to evaluate the accuracy and quality of the responses provided by the artificial intelligence model, ChatGPT, to questions about Herpes Zoster Ophthalmicus (HZO). HZO is a condition caused by the involvement of the ophthalmic branch of the trigeminal nerve, which can lead to severe ocular complications. Given the increasing use of artificial intelligence in healthcare, this study explores the capacity of ChatGPT to contribute to patient education on this disease. Methods: Seven questions selected by a dermatologist and an ophthalmologist from a list of twenty frequently asked questions about HZO were posed to the ChatGPT 4.0 model. The responses were evaluated using a four-point rating scale. Responses were independently rated as "excellent," "satisfactory with minimal explanation required," "satisfactory with moderate explanation required," or "unsatisfactory." The readability of the seven questions was assessed using the Flesch Reading Ease Score (FRES) and Flesch-Kincaid Grade Level (FKGL) criteria. Results: ChatGPT provided accurate and informative responses to all seven questions. Six responses were rated as "excellent," and one response was rated as "satisfactory with minimal explanation required". Inter-rater reliability was calculated using Cohen’s kappa, which was found to be 0.416 (95% confidence interval, 0.007, 0.825). A subsequent readability analysis using the Flesch Reading Ease Score (FRES) and the Flesch-Kincaid Grade Level (FKGL) revealed that the answers ranged from moderately difficult to challenging. The FRES values ranged from 41.13 to 57.24, while the FKGL scores varied from 9.8 to 13.3, suggesting a reading level corresponding to that of a high school to early college level. Conclusions: ChatGPT has demonstrated a strong capacity to effectively respond to patient questions about HZO. It was observed that it produced content suitable for readers educated at high school and university level and provided clear and detailed medical information. It can be used as a complementary tool for patient education, especially as a 24/7 resource for patients who have difficulty accessing healthcare services, following prior review by dermatologists and ophthalmologists.